If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + -8x + 8 = 0 Multiply x * x x2 + -8x + 8 = 0 Reorder the terms: 8 + -8x + x2 = 0 Solving 8 + -8x + x2 = 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '-8' to each side of the equation. 8 + -8x + -8 + x2 = 0 + -8 Reorder the terms: 8 + -8 + -8x + x2 = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -8x + x2 = 0 + -8 -8x + x2 = 0 + -8 Combine like terms: 0 + -8 = -8 -8x + x2 = -8 The x term is -8x. Take half its coefficient (-4). Square it (16) and add it to both sides. Add '16' to each side of the equation. -8x + 16 + x2 = -8 + 16 Reorder the terms: 16 + -8x + x2 = -8 + 16 Combine like terms: -8 + 16 = 8 16 + -8x + x2 = 8 Factor a perfect square on the left side: (x + -4)(x + -4) = 8 Calculate the square root of the right side: 2.828427125 Break this problem into two subproblems by setting (x + -4) equal to 2.828427125 and -2.828427125.Subproblem 1
x + -4 = 2.828427125 Simplifying x + -4 = 2.828427125 Reorder the terms: -4 + x = 2.828427125 Solving -4 + x = 2.828427125 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 2.828427125 + 4 Combine like terms: -4 + 4 = 0 0 + x = 2.828427125 + 4 x = 2.828427125 + 4 Combine like terms: 2.828427125 + 4 = 6.828427125 x = 6.828427125 Simplifying x = 6.828427125Subproblem 2
x + -4 = -2.828427125 Simplifying x + -4 = -2.828427125 Reorder the terms: -4 + x = -2.828427125 Solving -4 + x = -2.828427125 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = -2.828427125 + 4 Combine like terms: -4 + 4 = 0 0 + x = -2.828427125 + 4 x = -2.828427125 + 4 Combine like terms: -2.828427125 + 4 = 1.171572875 x = 1.171572875 Simplifying x = 1.171572875Solution
The solution to the problem is based on the solutions from the subproblems. x = {6.828427125, 1.171572875}
| 9/3[6*4/8] | | X=4y-y^6 | | x*log(X)=3000 | | X^2-4x+4+y^2+2y+1=9 | | 5x^2+3x-120=0 | | 12-2/5x=4 | | 5y-12=x | | 6(x-3)=5x-1 | | 7*8-6=g | | 9x-3=4x+18 | | 8+2*5=m | | (-7)+(-9)= | | 3y^3+4y^2-6x-8=0 | | 7(x-4)=12 | | f(x)=ln(x^2-5*x+6) | | 4(b-6)=6 | | fx=8cos(-x/4) | | 10+5y=4 | | 7(1/2)*x=7/8 | | 7(1/2)^x=7/8 | | 8x-15=5x-12 | | -x-2=-4x+7 | | q+2=6q | | 6q+0(1-q)= | | 2(3a+6)=4(3-7a)+6a | | f(x)=5e^2x-e | | 3q+2(1-q)= | | 6x+16=10x+44 | | 1.6(x-3)=-80 | | .6*x+4=7 | | 4x-13-6x+4=3-9X-7+3x | | 8x-2=4y |